Mood System of Joe Biden’s Speech on The Covid-19 Vaccination Program - Dian Luthfiyati; Oikurema Purwati; Widyastuti (ELITE JOURNAL, 2023)
ABSTRACTIn this study, the language that is utilized for communication is analyzed. In particular, the mood system is used in this study to examine Joe Biden's speech on the COVID-19 vaccination from the SFL perspective. To put it another way, this study examines the interpersonal meaning of speech, which can be used to investigate the speaker's attitude and evaluation of what is said in the speech. Through an in-depth examination of the mood system, this study attempts to explain the meaning of Joe Biden's speech in terms of interpersonal meaning. Although the majority of this study is qualitative, some descriptive quantification will be used to help it better understand the trends in the speaker's interpersonal meaning to help it better answer the research objectives. To assess the research data, it employs the Hallidayan theory of Systemic Functional Grammar (SFG). The information was obtained from publicly available websites. The researcher uncovered 81 pieces of data in Joe Biden's speech. The actual data is produced by a mood system that is divided between 75 declarative data and 6 imperative data. Analysis revealed that Joe Biden primarily used declarative. Declarative was utilized by Joe Biden throughout his speech to convey information to the audience. The majority of the material being supplied relates to immunization programs. Jokowi wants the audience to receive the COVID-19 vaccination program. Keywords: mood, the speech of Joe Biden, Systemic Functional Linguistics